TO CUT OR NOT TO CUT. ANTIBIOTIC USE IN ACUTE APPENDICITIS IN ADULT, PREGNANT AND PEDIATRIC POPULATIONS. REVIEW - Dorota Maria Komuńska,; Natalia Bukała,; Dominika Kondyjowska,; Weronika Tomasiczek,; Sylwia Tomasiczek,; Zuzanna Sawiec,; Ewa Antonowicz,; Marta Rogozińska, (International Journal of Innovative Technologies in Social Science, 2025)
Background. Acute appendicitis is one of the most common and routinely performed emergency surgeries in a wide range of populations. Appendectomy is commonly considered as the one and only solution for acute appendicitisResearch objective. This review aims to raise awareness on different approaches to treating acute appendicitis, comparing antibiotics and surgery treatment strategies.Material and methods. We searched PubMed and ReaserchGate databases, as well as current editions of renowned surgery textbooks for systematic reviews, articles, studies and meta-analyses surrounding the topic of treatment strategies and their complications for acute appendicitis in different populations.Results. In the adult population a higher success rate for surgical treatment was reported (82,3%) than the antibiotic one (67,2%). Antibiotic use in the pregnant population was associated with a lower rate of preterm deliveries, but an increased rate of infectious complications due to suspected immunological changes during pregnancy. In children, antibiotic treatment was associated with a 90,5% treatment success rate with histopathologically confirmed recurrence rate during the 1 year follow up of 16,1%.Conclusions. Surgery treatment offers a higher rate of treatment success than antibiotic management and lower recurrence rate. Conservative treatment may be more beneficial than surgery to specific groups of patients under the condition of confirmed uncomplicated appendicitis.